2015
DOI: 10.1016/j.febslet.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Benserazide, the first allosteric inhibitor of Coxsackievirus B3 3C protease

Abstract: Edited by Hans-Dieter KlenkKeywords: Coxsackievirus B3 3C protease Enzyme kinetics Non-competitive inhibitor Benserazide Allosteric binding site a b s t r a c t Coxsackievirus B3 is the main cause of human viral myocarditis and cardiomyopathy. Virally encoded Coxsackievirus 3C protease (3C pro ) plays an essential role in viral proliferation. Here, benserazide was discovered as a novel inhibitor from a drug library screen targeting Coxsackievirus 3C pro using a FRET-based enzyme assay. Benserazide, whose chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Thus, exploration of non-covalent inhibitors of picornaviral 3C pro s has already begun. Non-covalent inhibitors of RV 3C pro and CVB3 3C pro have been identified through fragment screening and FRET-based enzyme assay screening [ 136 ]. The chemical modification from water-insolubility to water-solubility shows a positive effect.…”
Section: Treatmentmentioning
confidence: 99%
“…Thus, exploration of non-covalent inhibitors of picornaviral 3C pro s has already begun. Non-covalent inhibitors of RV 3C pro and CVB3 3C pro have been identified through fragment screening and FRET-based enzyme assay screening [ 136 ]. The chemical modification from water-insolubility to water-solubility shows a positive effect.…”
Section: Treatmentmentioning
confidence: 99%
“…CVB3 has been consistently reported as the predominant pathogen causing human viral myocarditis, and current treatment approaches for patients with CVB3-related myocarditis are almost entirely supportive, as there is no vaccine or specific treatment for infections caused by coxsackieviruses [26]. In addition, HADV are the most common infectious cause of ocular disease worldwide, and HADV infections are associated with considerable morbidity and mortality, which could clearly be limited by the availability of effective antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Benz was identified as an HK2 inhibitor. Besides targeting the decarboxylase, Benz showed inhibitory effect against Coxsackievirus B3 3C protease [ 35 ]. Recent studies reported that the pretreatment of Benz enhanced the base-excision DNA repair of oxidative DNA damage in the presence of mutant breast cancer susceptibility gene 1 (BRCA1) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%